Avaliação in vitro da resistência à fratura de molares tratados endodonticamente com preparos cavitários MOD transfixados com um pino de fibra de vidro experimental - Henkes, Almir José (2017)
This study aimed to evaluate, in vitro, through the fracture strength testing, the influence of a fiberglass post position position, intracanal or horizontally transfixed, inserted in endodontically treated molars with MOD preparations and restored with composite resin and evaluate the fracture pattern after the mechanical test; and evaluate, through the fracture strength testing, the influence of a horizontally transfixed fiberglass post, inserted in endodontically treated molars with MOD cavity preparation and restored with Bulk Fill resins and to evaluate the fracture pattern after the mechanical test. In the first test, fifty extracted healthy molars were embedded in acrylic resin and divided into 5 groups (n = 10): G1(H) - sound; G2(CP) - cavity preparation (MOD) + endodontic treatment (E); G3 (R) - (MOD) + E + Z250 composite resin restoration (RS); G4- (RFP) (MOD) + E + fiberglass post into root canal + RS; G5 (FT) - (MOD) + E + fiberglass post horizontally transfixed + R; In the second test, ninety extracted molars were embedded in acrylic resin and divided into 9 groups (n = 10): G1) Sound (H); G2)cavity preparation (MOD); G3) MOD + root canal treatment (E); G4) E + Bulk fil composite resin (BF); G5) E + Bulk fill flow composite resin (BFF) + Z250 composite resin (250); G6) E + Z250; G7) E + transfixed fiberglass post (TP) + Z250 (Z250P); G8)E +TP+BF (BFP); G9) E + TP + BFF + Z250 (BFFP). The MOD cavity preparations were standardized with 2/3 width of the vestibular-lingual distance, with reference to the tip of the respective cusps, and occlusal-gingival depth of 4 mm, remaining 2 mm above the cement-cementum limit. The root canal treatments were performed in all groups, except for H group. Afterwards, the teeth were submitted to the fracture strength testing in a universal testing machine. After the mechanical test, the teeth were visually inspected to classify the fracture type as: pulp chamber floor (non-recoverable) or cusps (recoverable). Means (Newtons) followed by the same letter do not present statistical difference for ANOVA and Tukey´s test (p> 0.05): and for the first test, group (H) 5558N A; (E) 950N C; (R) 1715N C; (FC) 1723N C; (FT) 2621N B. The predominant pattern of fracture was in cusps, and for the second test, it was (H) 3930N a; (MOD) 957.3N d; (E) 611.2N d; (BF) 1103.3N d; (BFF) 978.3N d; (Z250) 1359.8 d; (Z250P) 2525N b; (BFP) 1891.4N bc; (BFFP) 2031.8N bc. The predominant failure mode was in pulp chamber floor (52.5%). The use of a horizontally transfixed fiberglass post (FT) in the first test showed the best fracture resistance recovery compared to the (E) group. The use of a fiberglass post into root canal, statistically, did not promote higher resistance to fracture (1723N) compared to the group restored with composite resin only (1715N). In the second test, Inserting a fiberglass post horizontally in molars endodontically treated and restoring with composite resins, Bulk Fill or conventional Z250, allowed higher fracture resistance than groups restored without post. The use of a fiberglass post decreased the occurrence of pulpal chamber floor fractures in endodontically treated molars.